Examination of the Relationship Between Psychological Resilience and Prosociality Levels and Naturalistic Decision-Making Skills of Physical Education Sports Teachers - Kenan KOÇ,; Mustafa Soner YÜCE, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose of this research is to determine the relationship between psychological resilience, prosociality levels, and naturalistic decision-making skills of physical education and sports teachers working in institutions affiliated with the Ministry of National Education in Kayseri province, as well as to examine comparisons between independent variables. The research model was constructed using descriptive and correlational survey models, which are quantitative research methods. 416 individuals, selected through random sampling method from those working in Kayseri province and its districts, voluntarily participated in the study. The data collection tools in the research consisted of the 'Brief Resilience Scale the 'Prosociality Scale', adapted into Turkish, the 'Naturalistic Decision-Making Scale', and a socio-demographic information form. In the bivariate comparisons of scores obtained from the scales, independent T-test statistics were used, while one-way analysis of variance (LSD) test statistics were employed for comparisons with more than two variables. Pearson Correlation analysis (r) was applied to reveal the relationship between the scores obtained from the scales. As a result of our study, it was determined that physical education and sports teachers exhibited high levels of psychological resilience, prosociality, and naturalistic decision-making skills. When examining the correlation results of our study, significant relationships were identified between the naturalistic decision-making scale and both the psychological resilience scale and the prosociality scale. Consequently, it can be stated that psychological resilience and prosociality concepts are factors that influence naturalistic decision-making skills.